Preservation Of Keroncong Music Through Music Learning At SMP Santa Angela Bandung (Universitas Negeri Semarang, 2021)
This study discusses the preservation of keroncong music through music learning at Santa Angela Junior High School in Bandung. Keroncong is a type of hybrid music, native to Indonesia, the result of acculturation between Portuguese music and Indonesian local music. Keroncong experiences a setback at the present time, especially among the younger generation. Through teaching and learning activities in schools one way keroncong music can be sustainable and developed. The focus of the problem that was studied included the keroncong music learning material, the learning methods used and the evaluation techniques used from the keroncong music extracurricular activities in Santa Angela Junior High School Bandung. This research uses a descriptive method with a qualitative approach. Based on research findings, learning keroncong music in extracurricular activities in Santa Angela Junior High School Bandung refers to three main materials namely the skill of playing the keroncong instrument, the skill of playing the keroncong rhythm, the keroncong songs. The benefit of this research is that it can provide innovation in learning keroncong music in schools as an effort to preserve and revitalize one of Indonesia's original music.